Um método para mensurar o grau de maturidade na tomada de decisão e-democrática - Maciel, Cristiano (2010)
Citizen participation in governmental affairs can make democracy a reality, since it generates a continuous flow of information between citizen and government while assisting in their decision-making. Nonetheless, for democracy to truly exist, citizens must articulate discourses, pitch in suggestions and proposals, deal with them, and indicate their choices by diffusing them to the public. Through e-democracy, these consultative and deliberative processes are granted visibility and are consolidated. The difficulties that emerge throughout this process refer to the fact that, when citizens are summoned to participate in public consultations and deliberative processes, the conversion of information from communication medias (television, newspapers, the Internet, among others) occurs individually. Such a process persists until the voting period. Thus, it is hard to verify the presence of a level maturity regarding the issues being discussed and deliberated that assures that the individual is truly exercising his role as a citizen. In order to render the integration of consultative and deliberative processes viable, the Government- Citizen Interactive Model is proposed and sorted into phases. The Democratic Interaction Language (DemIL) structures the debate, and the citizens are socialized in a virtual community. In order to diagnose the effectiveness of citizen participation in processes with e-democratic ends, the Maturity in Decision-Making method (MTD) is presented. This method constitutes a set of indicators that monitor the use and, consequently, mediate citizen behavior, providing the latter displays interest in participating in the deliberative process, registering, participating in discussions, casting votes, performing in a socializing environment, and consulting a library of information. At the end, the user satisfaction is measured. The experiments for checking the hypotheses of the research were developed by means of online surveys and a web application, the Democratic Citizen Community (CDC), which makes it possible to measure and classify the maturity level of each citizen assigned with making decisions. Finally, the citizens decision-making is classified as immature, somewhat mature, mature, or socially mature. By means of qualitative and quantitative analysis, one concludes that, among other aspects, the results of applying the MTD seem superior when applied to the CDC, since this provides the assessment of integrated resources, with dexterity in measuring maturity levels.